FORMULATION AND EVALUATION OF OPTIMISED MALTODEXTRIN BASED PRONIOSOME POWDERS CONTAINING BAZEDOXIFENE ACETATE FOR ORAL DELIVERY - GANDRA, SMITHA (International Journal of Current Pharmaceutical Research, 2020)
Objective: The main objective of the present study was to develop proniosomal formulations to enhance the oral bioavailability of bazedoxifene acetate by improving solubility, dissolution and/or intestinal permeability. Methods: Proniosomal powder formulations were prepared with bazedoxifene acetate drug varying the span 40 and cholesterol ratio in the range of 0.8:0.2 to 0.2:0.8 using maltodextrin as a carrier by slurry method. The prepared proniosomal powder was filled into capsules. The bioavailability enhancement of proniosomes loaded with drug was studied focusing on non-ionic surfactants composition and drug: span 40 ratio. Prepared proniosomes were characterized for their particle size distribution, zeta potential, entrapment efficiency, in vitro dissolution study and thermal characteristics to understand the phase transition behavior. Further, the formulated proniosomes were subjected to stability behavior, ex vivo permeation studies using rat intestine followed by in vivo studies. Results: Physico-chemical studies help in the optimization of formulations. Enhancement in dissolution is due to the incorporation of bazedoxifene acetate into the non-ionic surfactant and change in the physical state from crystalline to amorphous, thus improving oral bioavailability. Ex vivo studies show significant permeation enhancement across the gastrointestinal membrane compared to control. Conclusion: In conclusion, proniosomes provide a powerful and functional way of the distribution of inadequately soluble bazedoxifene acetate drug, which is proved from in vivo studies based on the enhanced oral delivery.